Poderes locais, devoção e hierarquias sociais: a Ordem Terceira de São Francisco de Mariana no século XVIII - Gustavo Henrique Barbosa (2015)
This work intends to understand the structural mechanisms of the social relationships and power in the Capitania of Minas Gerais during the second half of the 18th century, trying to identify the statutes developed and shared by the local elite. In order to do so, we have studied the insertion and functioning of the Third Order of Saint Francis of Mariana in the period between 1758 and 1808 a space created and maintained for the establishment of social and devotional relationships. We have assumed that the individuals, immersed in a certain sociocultural environment, give intelligibility to the action of the institution and configure its meanings. The method used consisted in constructing the social profile of the members to, departing from them, understand the work of the Third Order of Saint Francis of Mariana in all its organizational, social and institutional complexity. We have tried to demonstrate that being a third brother and also occupying a place at the institutions directive table allowed members to consolidate themselves as participants of the local elite which constructed and defended stratification criteria. By having relationships with other spaces of power, such as city councils, diocese and ordinances, the social qualities of the third brothers ended up transcending the Chapel where they used gather to elaborate the social statutes shared by the local elite.